An Empirical Study on Foreign Direct Investment In India And Its Impact on The Economy - Priyajit Ray (AG Volumes, 2021)
Foreign Direct Investment (FDI) is simply an investment from one individual or business entity to any other nation. FDI happens and takes place when a industry takes the ownership in a business entity in any another nation and thereby it is very much important for a developing economy like India such that our country can develop and grow. Foreign Direct Investment is not as simple as it looks like and it has got some socio economic significance as well which urged the researcher to conduct the study. Therefore, the researcher made an attempt to study the impact of FDI in our economy. Here, correlation and regression analysis was conducted by the researcher to establish an empirical relationship between the dependent and independent variables. At first correlation was conducted to find the association between the dependent and independent variables and based on that regression analysis was done to test the research hypothesis of the study and also to establish an empirical relationship between them. On the basis of the results of the statistical tests used, it was clearly found that the foreign direct investment in our country do have a significant impact in our economy and it is very much responsible in a way for the growth and development of our nation. Logical conclusion was given by the researcher on the basis of the findings of the study, and along with that scope for future researchers in the concerned area has also been provided such that it can be implied effectively in future for the nation’s development and sustainability.